Inclusion of Individuals with Disabilities through Assistive Technology at Workplace - Devpriya Dey, Dr. R Prakash Babu (International Journal of Advanced Science and Technology, 2020)
Assistive Technology (AT) requires an accommodation based on a system or a computer that allows a person with disability to work through or compensate for a impairment and improve person capability (Goddard, 2004). This research is conducted to identify the various assistive technologies applicable for the persons with disabilities (PwD) at work place. This study aims at understanding the key aspects such as inter communication technologies (ICT’s) which is result of disruption of technology making assistive technologies cost effective. The study also highlights the role of assistive technologies in accommodating PwD at workplace. The barriers that the PwD and the employers face in implementing the assistive technologies at work place have been explored to an extent. Lastly the research comprises of general disability issues and provides recommendations for disability accommodation guidelines for assistive technology at work place. An exploratory research approach has been adapted to gain a better understanding about research objectives. The data collection methodology is based on secondary data available from various reports and research papers. The analysis is purely qualitative in nature. This research would result in understanding the role of assistive technologies in accommodating PwD at workplace and means to overcome the barriers in implementing assistive technologies